Ecological Survey of Grasslands at Dudhwa National Park - Chaturvedi, A. N.; Misra, C. M. (Indian Forester, 1985)
The present study includes ecological survey of grasslands at Dudhwa National Park. Category-wise area of the park was evaluated with the help of satellite remote sensing techniques. Five (5) different types of grassland communities were identified and by the clip-guadrat method of 1 m2, quantitative and qualitative characters of each community were evaluated. The study reveals that grassland system of the park is quite productive in terms of biomass. However, planting of palatable and nutritive species will further improve the whole system in order to maintain the proper food-chain of the park.